Simultaneous positron emission tomography and ultrafast ultrasound for hybrid molecular, anatomical and functional imaging. (February 2018) - Provost, Jean; Garofalakis, Anikitos; Sourdon, Joevin; Bouda, Damien; Berthon, Béatrice; Viel, Thomas; Perez-Liva, Mailyn; Lussey-Lepoutre, Charlotte; Favier, Judith; Correia, Mafalda; Pernot, Mathieu; Chiche, Johanna; et al.
Abstract Positron emission tomography–computed tomography (PET–CT) is the most sensitive molecular imaging modality, but it does not easily allow for rapid temporal acquisition. Ultrafast ultrasound imaging (UUI)—a recently introduced technology based on ultrasonic holography—leverages frame rates of up to several thousand images per second to quantitatively map, at high resolution, haemodynamic, biomechanical, electrophysiological and structural parameters. Here, we describe a pre-clinical scanner that registers PET–CT and UUI volumes acquired simultaneously and offers multiple combinations for imaging. We demonstrate that PET–CT–UUI allows for simultaneous images of the vasculature and metabolism during tumour growth in mice and rats, as well as for synchronized multi-modal cardiac cine-loops. Combined anatomical, functional and molecular imaging with PET–CT–UUI represents a high-performance and clinically translatable technology for biomedical research. A system that combines positron emission tomography, computed tomography and ultrafast ultrasound allows for simultaneous multi-parametric imaging in animal models.